In vivo Emergence of Colistin and Tigecycline Resistance in Carbapenem-Resistant Hypervirulent Klebsiella pneumoniae During Antibiotics Treatment - Chen, Jiawei; Zeng, Yu; Zhang, Rong; Cai, Jiachang (Frontiers in Microbiology, 2021)
Three carbapenem-resistant Klebsiella pneumoniae (CRKP) (strains KP-426, KP-C76, and KP-CT77) were isolated from a patient with severe burns during the treatment of colistin and tigecycline. SNP typing showed that three ST11 CRKP were clonally related. Three isolates harbored the same set of antimicrobial resistance genes. blaKPC-2, blaSHV-12, blaTEM-1, and rmtB genes were located on the same 128,928-bp IncFII/IncR plasmid. tet(A), catA2, sul2, and dfrA14 genes were located on a plasmid with an unknown Inc-type. blaSHV-11, fosA, and aadA2 were chromosomal genes. An IS1 and an ISKpn14 were found in the promoter region of the mgrB gene of two colistin-resistant CRKP, K. pneumoniae KP-C76 and KP-CT77, respectively. A novel amino acid substitution, G300E, was identified in the type 1 Tet(A) variant of K. pneumoniae KP-CT77 which exhibited high-level tigecycline resistance compared to strains KP-426 and KP-C76 (MIC of 32, 4, and 4 mg/L, respectively). Conjugation and cloning experiments confirmed that the mutated Tet(A) resulted in a 4-fold increase in tigecycline MIC of Escherichia coli. Three CRKP belonged to the K64 serotype and possessed a similar IncHI1B/repB virulence plasmid carrying rmpA, rmpA2, and iucABCDiutA. The survival rates of Galleria Mellonella injected with K. pneumoniae KP-426, KP-C76, and KP-CT77 were 4.2%, 20.8%, and 8.3%, respectively. The emergence of colistin and tigecycline resistance in CR-hvKP posed a serious threat to clinical anti-infective therapy. The type 1 Tet(A) variant carrying G300E mutation, which conferred significantly elevated tigecycline MIC and was located on a conjugative plasmid, needs attention.